'Go in peace - and die!' The task of the church in the HIV and/or AIDS context - Van Dyk, Aletta Christina (Verbum et ecclesia, 2017)
The purpose of this study was to investigate how the white Afrikaans-speaking churches in the Reformed tradition are dealing with the health and well-being of its parishioners in the HIV and/or AIDS context. An electronic questionnaire was filled in by 142 clergy from various Afrikaans-speaking churches. Results showed that clergy (90%) believed that HIV and/or AIDS is a much bigger problem outside the Afrikaans-speaking church than inside the church. Although 66% agreed that HIV was also a problem in white Afrikaans-speaking churches, only 30% admitted that it was a problem in their own congregation. Most (70%) believed that HIV and/or AIDS can be ignored in their own congregations. A small number of clergy took it on themselves to provide HIV and/or AIDS counselling (21%), care (19%) and education (18%) with minimum support from church leaders. When it came to HIV and/or AIDS prevention, most clergy were only prepared to preach abstinence and faithfulness, with their main message that our bodies are the temple of God and that it should not be violated' (70%). Is it not time for clergy to confront reality and to protect their flock by also teaching them prevention skills?Intradisciplinary and/or interdisciplinary implications: The article is relevant to the fields of pastoral care, psychology and HIV and/or AIDS.